2021
DOI: 10.3280/fr2021-002004
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reporting: Much ado about nothing?

Abstract: Integrated reporting, which helps companies to share their value creation pro-cesses with their stakeholders, has developed rapidly in recent years. Due to the increased attention paid to the International Integrated Reporting Framework is-sued by the International Integrated Reporting Council, the number of companies worldwide engaging in integrated reporting is continually rising, which is presuma-bly driven by the claimed benefits of this practice. Through recourse to legitimacy theory and management fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The academic literature on IR attributes many benefits to the adoption of IR (Vitolla et al , 2019), although previous research has indicated that these presumed benefits are not always substantiated with evidence (De Graaff et al , 2021). The IIRC promotes many of these organizational benefits as positive effects of IR adoption, dividing them into two categories: connectivity benefits and performance benefits.…”
Section: Literature Review Theoretical Framework and Proposition Deve...mentioning
confidence: 99%
“…The academic literature on IR attributes many benefits to the adoption of IR (Vitolla et al , 2019), although previous research has indicated that these presumed benefits are not always substantiated with evidence (De Graaff et al , 2021). The IIRC promotes many of these organizational benefits as positive effects of IR adoption, dividing them into two categories: connectivity benefits and performance benefits.…”
Section: Literature Review Theoretical Framework and Proposition Deve...mentioning
confidence: 99%
“…The principal focus within the domain of IR research lies within the external reporting field (Dimes and De Villiers, 2020;De Graaff et al, 2021;IMA, 2021;. Although there is emergent literature on integrated thinking, it nevertheless still remains in its infancy (Busco et al, 2021).…”
Section: Development Of the Research Questionmentioning
confidence: 99%
“…The academic literature on IR attributes many benefits to the adoption of IR (Vitolla et al, 2019), although previous research has indicated that these presumed benefits are not always substantiated with evidence (De Graaff et al, 2021). The IIRC promotes many of these organisational benefits as positive effects of IR adoption, dividing them into two categories: connectivity benefits and performance benefits.…”
Section: Organisational Benefitsmentioning
confidence: 99%
See 2 more Smart Citations